2022
DOI: 10.3389/fpsyg.2021.767922
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relationships and Depressive Symptoms Among Adolescents: Results From the German BELLA Study

Abstract: Background: Poor mental health affects adolescent development and is associated with health and social outcomes in later life. The current study uses cross-sectional data to explore the understudied aspects of peer relationships as a predictor of depressive symptom severity of adolescents in Germany.Method: Data from the German BELLA study were analyzed. We focused on the most recent measurement point of the BELLA study and analyzed data of 446 adolescents (aged 14–17 years). Peer relationship was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(64 reference statements)
0
6
0
Order By: Relevance
“… Control Variable. Some existing studies have shown that personal characteristics of adolescents, such as gender, age, and educational background, have a significant impact on their peer relationships ( Adedeji et al, 2022 ). Meanwhile, family environmental factors such as only child, single parent family, living in rural or urban areas, family size, and yearly family income have a significant impact on adolescent peer relationships ( Boele et al, 2019 ; Livazović and Ham, 2019 ; Jambon and Malti, 2022 ).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“… Control Variable. Some existing studies have shown that personal characteristics of adolescents, such as gender, age, and educational background, have a significant impact on their peer relationships ( Adedeji et al, 2022 ). Meanwhile, family environmental factors such as only child, single parent family, living in rural or urban areas, family size, and yearly family income have a significant impact on adolescent peer relationships ( Boele et al, 2019 ; Livazović and Ham, 2019 ; Jambon and Malti, 2022 ).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Social support is the emotional, psychological, physical, informational, instrumental, and material assistance provided by others to maintain one's health or to facilitate one's adaptation to difficult life events (Dunst et al, 1986). Ecosystem theory suggests that the environment to which adolescents are exposed is not limited to the family, but peers and teachers in school also play important roles in their psychological development (Teresa et al, 2021;Adekunle et al, 2022), reflected primarily in social support. There is a discrepancy between the social support objectively provided by the outside world and the social support subjectively perceived by adolescents.…”
Section: Social Support As a Mediatormentioning
confidence: 99%
“…Higher levels of depression have been shown to be associated with greater difficulties in adapting to school life and interpersonal relationships [14]. In particular, adolescents experience more depression and anxiety when their peer relationships, which are an important part of their interpersonal relationships, are negative [15][16][17]. Among adolescents' interpersonal interactions, it has been found that stress from friend relationships increases depression [18], and increased stress and depression in adolescents result in smartphone overdependence, social network services (SNS) addictions, video game addictions, and habitual drug use [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased stress and depression in adolescents have been shown to increase suicidal ideation, which is a psychological problem. Loneliness is a major predictor of suicidal ideation in adolescents [19], and the relationship between depression, suicidal ideation, and loneliness has been discussed in several studies [5,15,19]. The factors that affect depression in adolescents include sociodemographic factors, home-environment-related factors, and educationalenvironment-related factors [20].…”
Section: Introductionmentioning
confidence: 99%